Can Minimum Prices Assure the Quality of Professional Services? - Georg Meran; Reimund Schwarze (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
This papers studies the effects on service quality and consumer surplus of a minimum price which is fixed by a bureaucratic non-monopolistic professional association. It shows that the price floor set by a Niskanen-type professional assocation will maximize consumer surplus only if consumers demand the highest possible average quality. If consumers demand services of lesser quality, the association?s price floor will be too high if measured by consumer surplus. Moreover we show that a de-regulated market will always reproduce the favorable result of a uniformly high price in the case of top quality demand while delivering superior results in the case of a mixed demand for high and low quality services. The general picture that emerges from this discussion is that the current EU Commission?s initiative to abolish fixed price schemes for professional services will not lead to a decrease in quality that would be undesirable from a standpoint of consumer protection. This holds even if we acknowledge the opponent?s claim that there is a chance of deprivation of professional ethics due to price competition.
Keywords: J44; L15; K21; 330; Liberal professions; price regulation; quality; professional association; self-regulation; EU competition policy; intrinsic motivation